2021
DOI: 10.1370/afm.2627
|View full text |Cite
|
Sign up to set email alerts
|

Medical Practice Variation Among Primary Care Physicians: 1 Decade, 14 Health Services, and 3,238,498 Patient-Years

Abstract: PURPOSE Variation in medical practice is associated with poorer health outcomes, increased costs, disparities in care, and increased burden on the public health system. In the present study, we sought to describe and assess inter-and intra-primary care physician variation, adjusted for patient and clinic characteristics, over a decade of practice and across a broad range of health services. METHODSWe assessed practice patterns of 251 primary care physicians in southern Israel. For each of 14 health services (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…CHS has a centralised comprehensive computerised database of electronic healthcare records that receives continuous real-time input from the medical, laboratory, pharmaceutical, vaccination and hospitalisation operating systems, and can be accessed down to the individual patient. The dataset, based on reports from both hospitals and outpatients clinics, has been shown previously to have high validity and reliability 13 14…”
Section: Methodsmentioning
confidence: 99%
“…CHS has a centralised comprehensive computerised database of electronic healthcare records that receives continuous real-time input from the medical, laboratory, pharmaceutical, vaccination and hospitalisation operating systems, and can be accessed down to the individual patient. The dataset, based on reports from both hospitals and outpatients clinics, has been shown previously to have high validity and reliability 13 14…”
Section: Methodsmentioning
confidence: 99%
“…Unwarranted variations in patient care have been documented for virtually every major medical condition across multiple disciplines and are associated with negative patient outcomes and increased healthcare costs. [1][2][3][4][5] For instance, in a Toronto-based study, our team found a 62% relative difference in inpatient mortality between the lowest and highest quartiles of internists in seven academic hospitals; in the same study, significant variations were also found in length-of-stay, use of diagnostic imaging and readmission rates. 3 Other examples of physician-level practice variations and patient outcomes have been documented in general surgery, emergency medicine (EM) and primary care.…”
Section: Introductionmentioning
confidence: 89%
“…For instance, in a Toronto-based study, our team found a 62% relative difference in inpatient mortality between the lowest and highest quartiles of internists in seven academic hospitals; in the same study, significant variations were also found in length-of-stay, use of diagnostic imaging and readmission rates 3. Other examples of physician-level practice variations and patient outcomes have been documented in general surgery, emergency medicine (EM) and primary care 2 4 6…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Hence, the CHS dataset represents Israel's general population in Israel and has been previously shown to have provided highly valid and reliable estimates. [9] The CHS central computerized database is subjected to a continuous validation method based on electronic Personal Health Records (PHR) gathered from CHS systems. The diagnoses are inserted into these PHR by CHS physicians.…”
Section: Methodsmentioning
confidence: 99%